2006
DOI: 10.1111/j.1399-0004.2006.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications and limitations of empiric data in provision of recurrence risks for schizophrenia: a practical review for healthcare professionals providing clinical psychiatric genetics consultations

Abstract: Schizophrenia is a common disorder that may frequently be encountered when taking family histories in the genetics clinic, whether or not the referral is for a psychiatric indication. Like in other common disorders, the provision of recurrence risks for schizophrenia is a complex clinical issue because empiric recurrence risks (while reasonably well established) can rarely be used without individual tailoring. This review seeks to identify and detail some pertinent issues surrounding the clinical utility of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 84 publications
0
35
0
2
Order By: Relevance
“…Respondents in this study reported being more willing to discuss a family history of schizophrenia if an individual risk calculation could be provided, thus implying that respondents felt that this is currently not possible. Although it can be challenging, individualized risk assessment for psychiatric illnesses can be performed: empiric risks are available and can be modified according to factors that have been detailed elsewhere [13]. Thus, genetic counselors’ practice might perhaps be enhanced by further education in this area [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents in this study reported being more willing to discuss a family history of schizophrenia if an individual risk calculation could be provided, thus implying that respondents felt that this is currently not possible. Although it can be challenging, individualized risk assessment for psychiatric illnesses can be performed: empiric risks are available and can be modified according to factors that have been detailed elsewhere [13]. Thus, genetic counselors’ practice might perhaps be enhanced by further education in this area [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Families often want an explanation as to why their family member became ill, may be interested in risks for other family members to become similarly affected or may have questions regarding their own risk that can be addressed by using empiric data as a basis for individualized risk assessment [13]. …”
Section: Introductionmentioning
confidence: 99%
“…For patients who have questions beyond the knowledge base of their psychiatrists referral for consultation by genetics professional is appropriate. 14 The prospects of genetic testing Will genetic testing be feasible for psychiatric illness? In theory there is a scenario in which testing could be applied in schizophrenia.…”
Section: Individualizing Risksmentioning
confidence: 99%
“…It is also important to remember that the perceived magnitude and impact of risks and probabilities may vary greatly from person to person. 14 After genetic counselling there should be an improved understanding of the following issues:…”
Section: Individualizing Risksmentioning
confidence: 99%
“…Assessing risk for psychotic illness in relatives is further complicated by two other factors: 1) different source studies for empiric data tend to generate slightly different numeric probabilities, and 2) empiric data represent probabilities for individuals to develop illness, which are influenced by complex sets of variables (including individual, family, genetic, and environmental factors). The cumulative effect of these factors is that, when assessing risk, deriving a single discrete numeric probability for an individual to develop psychotic illness is rarely possible or adequate (Austin and Peay, 2006;Austin et al, 2008). Instead, probability empiric data should ideally be presented in the context of confidence intervals, and discussion of how they can be personalized according to aspects of the presenting individual's family history.…”
Section: Introductionmentioning
confidence: 99%